Subsurface structures of Sianok Segment in the GSF (Great Sumatran Fault) inferred from magnetic and gravity modeling - Dahrin, Darharta; Amir, Harman; Suryanata, Putu Billy; Bijaksana, Satria; Fajar, Silvia Jannatul; Ibrahim, Khalil; Harlianti, Ulvienin; Arisbaya, Ilham; Pebrian, Mutiara Qalbi; Rahman, Adinda Aisyah; Kasendri, Adibbian (Frontiers in Earth Science, 2022)
Among the 19 segments of the Great Sumatran Fault (GSF), the Sianok segment is unique due to its proximity to active volcanoes as well as to the sizable Maninjau Caldera. Located next to the Sumani to its southeast, the Sianok segment also passes through a relatively densely populated area. To identify potential disasters in the future, it is imperative to understand the subsurface structures of the Sianok segment. In this study, ground magnetic measurements were conducted, and the data were combined with the Bouguer anomaly map. Hand samples were also collected and measured for magnetic susceptibility and density. The values were later used as initial parameters for modeling. Joint forward modeling of magnetic and gravity was then used in the modeling stage as well as in the interpretation stage. Subsurface models of 20 km in depth were then formulated based on the magnetic and gravity data. The models show shallow magma chambers beneath Maninjau Caldera, Mount Marapi, and Mount Singgalang-Tandikat. The models confirm that exposed and unexposed Permian metamorphic rocks are commonly distributed in the Sianok segment. The thickness of volcanic deposits such as tuff and andesites in the Sianok segment were found to be sizable, ranging from 1 km for tuff to 3.5 km for andesites of the Maninjau Caldera.